An Investigation of Male and Female Teachers’ Oral Feedback in English Classroom: A Focus on Elicitation & Reformulation - Khairisya, Thahira; Fithriani, Rahmah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The primary goal of this study is to analyze the elicitation and reformulation used by male and female teachers in English classes. In this descriptive qualitative study, the researcher collected data from observation and in-depth interviews in three class meetings for 135 minutes (45 minutes/meeting). Ten teachers, five male, and five female, from one Madrasah Tsanawiyah Negeri in Medan City, North Sumatra. The data were analyzed using Tsui's Elicitation and Martinot's Reformulation categorization. The findings reveal that male and female teachers similarly use five elicitation types: inform, confirm, agree, repeat, and clarify, where the most dominant type of elicitation is confirmed. In addition, three different types of reformulation were found in the reformulation feedback: the same construction, transformation, and restructured statements. In contrast, transformation was the dominant type used by the teachers. In practicing oral feedback, especially elicitation, male teachers use standard language to elicit the students' utterances, while female teachers ask students to make the teaching and learning process interactive. In reformulation, the study results show that male teachers only provide oral feedback by giving instructions, while female teachers provide oral feedback by giving instructions and reformulating utterances. Furthermore, three main reasons were found for teachers to provide oral feedback, namely: to detect mistakes made by students, to stimulate students to interact with the teacher, and to create reflective and effective feedback practices.